Diversity and variation of dorsal carapace structures in the giant armadillo Priodontes maximus (Kerr, 1792) and their potential use for individual identification - Barasoain Goñi, Daniel (2021)
Dorsal carapace and osteoderm morphological features have traditionally been widely used inboth extinct and extant armadillo systematics. However, the intraspecific variability at the carapace level represents a little studied aspect. In this contribution, we analyzed several dorsal carapaces of Priodontes maximus with the purpose of recording such variability. As a result, we describe a total of seven structures concerning the dorsal carapace osteoderm configuration, including distinct terminations of the osteoderm rows, and the most frequent aberrant shapes of the osteoderms. Though the same type of structure can be usually found in several specimens, its frequency and precise location within the carapace are unique to each individual. In this sense, besides improving anatomical descriptions, the identification of these structures can be potentially implemented as a complementary method to help recognize specific individuals being tracked. Moreover, it can represent a very effective recognition method even a long time after death. Given the general decreasing trend of P. maximus populations, it is important to develop as many monitoring tools as possible, in order to support conservation programs for this species.